Complete mitochondrial genome of the Ye's spiny-vented frog Yerana yei (Anura: Dicroglossidae). (June 2015) - Chen, Zhuo; Zhai, Xiaofei; Zhu, Yanjun; Chen, Xiaohong
Abstract Yerana yei (Anura: Dicroglossidae) is the only one species in the genus Yerana and the taxonomy of the Y. yei remains unresolved and controversial. The complete mitochondrial genome of Yerana yei (Anura: Dicroglossidae) was sequenced in the present study, and it is a circular molecule of 17, 072 bp in length and contains the 38 genes typically found in other anurans: 13 protein-coding genes, 2 ribosomal RNA genes and 23 transfer RNA genes (including an extra copy of tRNAMet). The order and orientation of the genes is the same as that found in other Paini species. The A + T content of the overall base composition of H-strand is 58% (T, 29.4%; C, 27.3%; A, 28.6%; G, 14.7%) and the length of control region is 1580 bp with 67% A + T content.